Democracy and human rights in international law: regional perspectives on universal ideas - Burchill, Richard (1999)
This thesis investigates the development of democracy as a principle of international law, primarily from the view of human rights law, with the purpose of developing a basis for an international law of democracy. It begins with the proposition that the international legal argument prevents current international human rights law, and a future international law of democracy, from being effective for the individual, for whom the law is supposed to benefit. Under the present arrangement human values do not have a great impact upon the law as individuals are excluded from the law making process which remains an affair exclusive to states and governments. Furthering democracy as a legal principle will assist in making the law more effective as individuals are able to participate In the decisions impacting their lives. At the global level the development of democracy as a legal idea has remained primarily as rhetoric expressed in a number of diverse texts covering a wide range of international activity. The nature of democracy as an contestedtopic is demonstrated at the global level as the lack of agreement on its meaning and application have prevented the creation of substantive legal principles. At the regional level in Europe, the Americas and to a lesser degree Africa, existent intergovernmental organisations with a concern for human rights have made great strides in developing an international law of democracy for their specific region. Efforts in support of democracy globally and regionally are transforming international law in way that is more responsive to the needs and desires of individuals. Numerous obstacles hinder this progress but the large amount of rhetoric expressed in support of democracy and human rights provide individuals with the tools necessary to ensure the law does not remain only rhetoric.